DEVELOPMENT AND VALIDATION OF METHOD OF QUANTITATIVE DETERMINATION OF RESIDUAL ORGANIC SOLVENTS IN INNOVATIVE ACTIVE PHARMACEUTICAL INGREDIENT WITH GC-FID - E. V. Butina; S. A. Zaitsev; A. V. Basevich (Разработка и регистрация лекарственных средств, 2019)
The aim of the study was to develop and validate a new method of quantitative determination of residual organic solvents in a substance A using GLC. Studies were carried out with gas chromatography with a flame ionization detector and sampling from the vapor phase. The effect of the polarity of the stationary phase for the chromatographic separation of the organic solvents peaks: Chloroform, Ethanol, Methylene Chloride, Cyclohexane, Ethyl Acetate, Methanol, N, N-dimethylformamide, 2-propanol was investigated. Chromatographic separation of Ethanol, Methanol, 2-propanol, Ethyl Acetate, Methylene Chloride and Cyclohexane was performed with quartz capillary column DB-624, 30 m × 0.20 mm, 1.8 micron; Chloroform and N, N-dimethylformamide – DB-WAX, 30 m × 0.50 mm, 0.25 mm. System suitability criteria and the validity of method were determined. Method has high specificity, precision, linearity, sensitivity and reliability.